Between facts and norms: Testing compliance with Article 8 ECHR in immigration cases. Issue 2 (June 2019) - Klaassen, Mark
The European Court of Human Rights plays a subsidiary role in the protection of the rights and freedoms set forth in the Convention. To enable national authorities to perform their primary role, it is important that the Court offers sufficient guidance on the interpretation of the Convention. It has already been argued that the case law of the Court on the right to respect for family life in immigration cases, lacks consistency in terms of procedural and substantive protection. The inconsistency in the case law is mostly the case in the admission and regularisation case law. This manifests itself in specific issues including the determination of whether an interference has occurred as well as the court's determination of the best interests of the child. Consequently, the case law difficult to apply by national authorities which leads to widely diverging practices by the Contracting Parties. The objective of this article is to outline the differences and inconsistencies in the different forms of immigration cases and the corresponding compliance tests of the Court. The article aims to offer a solution that would enable both the Court and the Contracting Parties to differentiate the level of protection that is offered by Article 8 in immigration cases, while providing sufficient guidance to national decision-making authorities and judiciaries so that they can efficiently and effectively exercise the primary role they play in the protection of the right to respect for family life in immigration cases.